ASCOD Phenotyping of Stroke With Anterior Large Vessel Occlusion Treated by Mechanical Thrombectomy. Issue 12 (27th October 2021) - Fontaine, Louis; Sibon, Igor; Raposo, Nicolas; Albucher, Jean-François; Mazighi, Michael; Rousseau, Vanessa; Darcourt, Jean; Thalamas, Claire; Drif, Amel; Sommet, Agnes; Viguier, Alain; Guenego, Adrien; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Determining the mechanism of large vessel occlusion related acute ischemic stroke is of major importance to initiate a tailored secondary prevention strategy. We investigated using the atherosclerosis, small vessel disease, cardiac source, other cause, dissection (ASCOD) classification the distribution of the causes of large vessel occlusion related acute ischemic stroke treated by mechanical thrombectomy. Methods: This was a predefined substudy of the FRAME (French Acute Multimodal Imaging to Select Patient for Mechanical Thrombectomy). Each patient underwent a systematic etiological workup including brain and vascular imaging, electrocardiogram monitoring lasting at least 24 hours and routine blood tests. Stroke mechanisms were systematically evaluated using the atherosclerosis, small vessel disease, cardiac source, other cause, dissection grading system at 3 months. We defined single potential cause by one cause graded 1 in a single domain, possible cause as a cause graded 1 or 2 regardless of overlap, and no identified cause without grade 1 nor 2 causes. Results: A total of 215 patients (mean age 70±14; 50% male) were included. A single potential cause was identified in 148 (69%). Cardio-embolism (53%) was the most frequent, followed by atherosclerosis (9%), dissection (5%) and other causes (1%). Atrial fibrillation accounted for 88% of C1. Overlap between grade 1 causes was uncommon (3%). Possible causes were identified in 168 patients (83%) and 16 (7%) had no cause identified after the initial evaluation. Conclusions: Cardio-embolism, especially atrial fibrillation, was the major cause of large vessel occlusion related acute ischemic stroke. This finding emphasizes the yield of paroxysmal atrial fibrillation detection in those patients. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03045146.